Self-phase modulation and inter-polarization cross-phase modulation mitigation in single-channel DP-16QAM coherent PON employing 4D clustering - Costa, Camila [UNESP]; Borges, Lucio [UNESP]; Penchel, Rafael A. [UNESP]; Abbade, Marcelo L.F. [UNESP]; Giacoumidis, Elias; Wei, Jinlong; de Oliveira, Jose A. [UNESP]; Santos, Mirian [UNESP]; Li, Shi; Richter, André; Marconi, Jorge D.; Pita, Julián L.; et al. (My University, 2023)
Digital coherent reception has emerged as a potential solution for 100 Gbps passive optical networks (PONs). In this paper, we propose and analyze the simultaneous clustering of both polarizations in dual-polarization 16-ary quadrature amplitude modulation (DP-16QAM) to tackle the effects of the intra-polarization self-phase modulation and inter-polarization cross-phase modulation. Simulation results reveal that by processing the two polarizations, the performance of the nonlinear compensation is significantly enhanced. Thus, the proposed 4D clustering leads to range extensions of 13.6 km and 9 km for target bit error ratios of 10−3 and 10−2, respectively. Such range extension requires a block of around 8000 symbols and 5632 operations, which can be parallelized, requiring just 19 sequential operations.
Keywords: Clustering; Digital coherent optical communication systems; Nonlinear distortion